Regulation of Angiotensin-Converting Enzyme 2: A Potential Target to Prevent COVID-19? - Hu, Yue; Liu, Lihuan; Lu, Xifeng (Frontiers in Endocrinology, 2021)
The renin–angiotensin system (RAS) is crucially involved in the physiology and pathology of all organs in mammals. Angiotesin-converting enzyme 2 (ACE2), which is a homologue of ACE, acts as a negative regulator in the homeostasis of RAS. ACE2 has been proven to be the receptor of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which caused the coronavirus disease 2019 (COVID-19) pandemic. As SARS-CoV-2 enters host cells through the binding of viral spike protein with ACE2 in humans, the distribution and expression level of ACE2 may be critical for SARS-CoV-2 infection. Growing evidence shows the implication of ACE2 in pathological progression in tissue injury and several chronic conditions such as hypertension, diabetes, and cardiovascular disease; this suggests that ACE2 is essential in the progression and clinical prognosis of COVID-19 as well. Therefore, we summarized the expression and activity of ACE2 under various conditions and regulators. We further discussed its potential implication in susceptibility to COVID-19 and its potential for being a therapeutic target in COVID-19.